Radiology and imaging for medical students - Sutton, David, 1917-2002 (Churchill Livingstone, 1998)
This edition of the acclaimed introductory text comprehensively covers diagnostic radiology, concentrating on the common pathologies most likely to be encountered, including all of the latest developments in the field. It is generously illustrated, with new and better quality images, including examples of plain film radiographs and CT and MRI Scans.